A multidimensional construct of perceptions on sexual and reproductive health among Muslim undergraduate students - Sa-U, Samsoo; Nordin, Mohamad Sahari; Nik Abdul Rahman, Nik Suryani (Postgraduate Student Society IIUM, 2009)
This study examines factors influencing undergraduate students who are all Muslims from one of the public universities in Malaysia. Data were obtained from a survey conducted among the undergraduate students (n=255). Principle Components Analysis (PCA) revealed four latent factors: the electronic and printed media, knowledge of circumcision, the Islamic values on sexuality and their prior knowledge of sexual act. Based on the views of the respondents on the roles played by curriculum, religion and media in disseminating knowledge on sex-related matters, recommendations are drawn to assist the relevant parties in coming up with comprehensive sexuality education for Muslim adolescents.